Evaluation of physiological FDG uptake in the skeleton in adults: Is it uniformly distributed? - DEDE, FUAT; TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (ELSEVIER DOYMA SL, 2014)
Aim: The aim of this study was to study whether FDG was uniformly distributed throughout the skeleton and whether age and gender affected this biodistribution. Material and Methods: A total of 158 patients were included in this retrospective study. None of the patients had received prior treatment that had affected the bone marrow and patients with bone metastases, trauma, benign and/or malignant hematologic disorders were excluded from the study. The SUVmax from the 24 different locations in the skeleton was obtained and all the values were compared with each other. Results: FDG uptake in the skeleton was not uniform in both sexes. While the highest FDG uptake was seen in the L3 vertebra, the lowest glucose metabolism was observed in the diaphysis of the femur. Concerning the vertebral column. FDG uptakes were also non-uniform and the SUVmax gradually increased from the cervix to the lumbar spine. The mean skeletal SUVmax was decreased in accordance with age in both genders. Conclusion: FDG was not uniformly distributed throughout the skeleton in both sexes. It had a tendency to increase from the appendicular to axial skeleton and from cervical to lumbar spine in the vertebral column that may be related with the normal distribution of the red bone marrow. Additionally, the glycolytic metabolism of the whole skeleton was gradually decreased in accordance with the age in both sexes. (C) 2013 Elsevier Espana, S.L.U. and SEMNIM. All rights reserved.
Keywords: Bone marrow; Skeleton; Glycolytic metabolism; FDG; PET/CT; COLONY-STIMULATING FACTOR; BONE-MARROW; THERAPY; PET